Manajemen Pengemasan Produk terhadap Peningkatan Usaha Penjualan Krupuk Puli di Desa Ngampel Jomban - Athok Miftachuddin, Achmad Agus; Sufaidah, Siti; Mahmudin, Muhammad; Arifin, Mohammad Sholeh (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Puli crackers, a traditional Indonesian food, are popular across various demographics due to their crispy texture derived from a mixture of tapioca and rice flour. Despite their business potential for small and medium-sized enterprises (SMEs), such as that owned by Mr. Nyamin in Ngampel village, Jombang, the conventional packaging methods represent a barrier to enhancing product appeal. This community service activity was chosen due to the importance of improving packaging management to increase product competitiveness. The objective of this activity is to provide training and guidance to SMEs on managing packaging more effectively and attractively. Methods used include direct training sessions, consultations, and the application of modern packaging techniques with more appropriate tools and materials. The results of this activity demonstrate a significant improvement in packaging quality, enhancing both the visual appeal and durability of the product. Based on these outcomes, it can be concluded that improvements in packaging not only strengthen the product's position in the local market but also open up potential for expansion into broader markets, highlighting the importance of technological adaptation in the traditional food industry.